Advertising for the People: The History of the Social Democratic Party of Sweden's Own Advertising Company—Folkreklam and Förenade ARE-Bolagen, 1947–1997. (4th June 2020) - LAKOMAA, ERIK
Abstract : The Social Democratic Party not only ruled Sweden for most of the twentieth century but also owned one of the country's largest advertising groups. The company, founded in 1947 as Folkreklam and later renamed Förenade ARE-Bolagen, rapidly became dominant in outdoor advertising in Sweden and remained in that position until the late 1980s. This paper expands the previous research on party-owned enterprises, a type of businesses that is rare in the Western democratic world, covering the history of ARE from its inception to its eventual merger with JCDecaux in 1997. It is shown that the owner relationship with the party was highly beneficial for the company, as it provided preferential access to adverting space and public contracts from government agencies and municipalities without formal competition. The party benefited from the control over sensitive information pretraining to strategies in political propaganda during elections and from the financial contribution of ARE.